Effect of Intensive Blood Pressure Lowering on Left Ventricular Hypertrophy in Patients With Hypertension: SPRINT (Systolic Blood Pressure Intervention Trial). Issue 5 (1st August 2017) - Soliman, Elsayed Z.; Ambrosius, Walter T.; Cushman, William C.; Zhang, Zhu-ming; Bates, Jeffrey T.; Neyra, Javier A.; Carson, Thaddeus Y.; Tamariz, Leonardo; Ghazi, Lama; Cho, Monique E.; Shapiro, Brian P.; He, Jiang; et al.
Abstract : Background: It is currently unknown whether intensive blood pressure (BP) lowering beyond that recommended would lead to more lowering of the risk of left ventricular hypertrophy (LVH) in patients with hypertension and whether reducing the risk of LVH explains the reported cardiovascular disease (CVD) benefits of intensive BP lowering in this population. Methods: This analysis included 8164 participants (mean age, 67.9 years; 35.3% women; 31.2% blacks) with hypertension but no diabetes mellitus from the SPRINT trial (Systolic Blood Pressure Intervention Trial): 4086 randomly assigned to intensive BP lowering (target SBP <120 mm Hg) and 4078 assigned to standard BP lowering (target SBP <140 mm Hg). Progression and regression of LVH as defined by Cornell voltage criteria derived from standard 12-lead ECGs recorded at baseline and biannually were compared between treatment arms during a median follow-up of 3.81 years. The effect of intensive (versus standard) BP lowering on the SPRINT primary CVD outcome (a composite of myocardial infarction, acute coronary syndrome, stroke, heart failure, and CVD death) was compared before and after adjustment for LVH as a time-varying covariate. Results: Among SPRINT participants without baseline LVH (n=7559), intensive (versus standard) BP lowering was associated with a 46% lower risk of developing LVH (hazard ratio=0.54; 95% confidence interval, 0.43–0.68). Similarly, among SPRINT participants with baseline LVH (n=605, 7.4%), those assigned to the intensive (versus standard) BP lowering were 66% more likely to regress/improve their LVH (hazard ratio=1.66; 95% confidence interval, 1.31–2.11). Adjustment for LVH as a time-varying covariate did not substantially attenuate the effect of intensive BP therapy on CVD events (hazard ratio of intensive versus standard BP lowering on CVD, 0.76 [95% confidence interval, 0.64–0.90] and 0.77 [95% confidence interval, 0.65–0.91] before and after adjustment for LVH as a time-varying covariate, respectively). Conclusions: Among patients with hypertension but no diabetes mellitus, intensive BP lowering (target systolic BP <120 mm Hg) compared with standard BP lowering (target systolic BP <140 mm Hg) resulted in lower rates of developing new LVH in those without LVH and higher rates of regression of LVH in those with existing LVH. This favorable effect on LVH did not explain most of the reduction in CVD events associated with intensive BP lowering in the SPRINT trial. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01206062. Abstract : Supplemental Digital Content is available in the text.